STUDENTS' PREFERENCE ON USING ONLINE TRANSLATOR IN ACADEMIC WRITING - Hidayat, Agus (Raden Intan State Islamic University of Lampung, Indonesia, 2024)
This study investigates the preferences of fifth-semester students at UIN Raden Intan Lampung regarding the use of online translators in academic writing. Through a descriptive qualitative approach, data were collected from 180 students via a six-item questionnaire focusing on general usage and the impacts on academic writing. The findings indicate that online translators are widely utilized, with the majority of students using them daily or weekly. Google Translate emerged as the most preferred tool due to its ease of use and comprehensive language support. Students primarily use online translators to translate words or phrases, understand foreign texts, and check grammar and sentence structure. The impact on academic writing is generally positive, with many students finding these tools effective in improving their writing quality and efficiency. However, challenges such as over-reliance on translators, misinterpretation of context, and lack of technical vocabulary were also noted